Microstructure and hot deformation behaviour of high-carbon steel/low-carbon steel bimetal prepared by centrifugal composite casting. Issue 1 (September 2016) - Xu, Jianzhong; Gao, Xingjian; Jiang, Zhengyi; Wei, Dongbin; Jiao, Sihai
Abstract Bimetal consisting of high-carbon steel and low-carbon steel was prepared by centrifugal composite casting, and thermo mechanical treatments were carried out by hot compression tests using Gleeble 3500 thermo mechanical simulator. The characteristics of microstructure and hot deformation behaviour of the bimetal were investigated. It is concluded that a sound metallurgical bond was achieved by micro mass transfer across the interface between the constituent steels. Four different microstructural regions (including low-carbon steel region, interface region, fully pearlitic region and pro-eutectoid ferritic/pearlitic region) with different mechanical properties were found, which resulted in heterogeneity of plastic deformation within the bimetal. Regardless of strain rate, the low-carbon steel layer preferentially extruded from the bimetal when deformation temperature was below 900 °C, whereas the extrusion was not observed at 900, 1000 and 1100 °C. This indicated that the high-carbon steel/low-carbon steel bimetal can be processed like monolithic material.